Improvement of low-cost attendance monitoring system using Raspberry Pi - Amirul Ezzat, Bin Mohamed Riduan. (Universiti Malaysia Sarawak (UNIMAS), 2017)
Every year, the number of students in Universiti Malaysia Sarawak is increasing and to deal with the everyday attendance of these students, a new system for attendance monitoring in Faculty of Engineering is required. Therefore, this project propose the automatic attendance system based on Quick Response code scanning. This project design involves the image of a QR code being scanned, decoded and the information is saved in a database. The QR code scanning method is proposed because it is simple and affordable. The students can easily scanned the QR code provided to them using the webcam attach to the raspberry pi and the camera will capture the image of the respective QR code. The program will then decode it and the information is saved in the database. There are two systems involve in this project in which the first one require the QR code to be scanned and the other part is storing the information in the database. The microcomputer used in this project is Raspberry Pi 2 model B. This project consists of two parts, hardware and software. The hardware part consists of the Raspberry Pi microcomputer and the attachment of Raspberry Pi camera module to the microcomputer to act as a scanner for the QR code. The software part consists of the python programming for the Raspberry Pi microcomputer. The expected outcome of this project is to be able to capture the image of the QR code along with decoding it and to create a working database to store the information and analyse the attendance.